Non-invasive markers for prediction of varices in patients with portal hypertension - Chandail, Vijant Singh; Kotwal, Suman Kumar; Koul, Shanky; Gupta, Rajesh; Mahajan, Annil (International Journal of Research in Medical Sciences, 2017)
Background: The incidence of esophageal varices in patients with cirrhosis ranges from 35 to 80%. Thus, screening all cirrhotic patients with upper gastrointestinal (UGI) endoscopy to detect the presence of varices implies a number of unnecessary endoscopies, which increase the workload of endoscopy units and UGI endoscopy has its own limitations. The present study was conducted to investigate series of non-invasive biochemical and radiological markers for prediction of esophageal varices in patients with portal hypertension. Methods: Patients of either sex, aged 18-80 years with diagnosis of chronic liver disease, cirrhosis, extrahepatic portal vein obstruction or any other cause of portal hypertension were studied. Patients were subjected to UGI endoscopy within 2 weeks of investigation of laboratory parameters. All patients were subjected to detailed clinical history and physical examination and biochemical and radiological investigations. Endoscopy was done with an olympus gastroscope using 20% xylocaine spray. Results: Out of 51 patients in the study, esophageal varices were seen in 34 (66.67%) patients and absent in 17 (33.33%) patients. On multiple logistic regression analysis, the variables independently linked to the presence of esophageal varices were; spleen diameter [odds ratio (OR): 1.137, 95% confidence interval: 1.033-1.255; p=0.009] and Portal vein size [odds ratio (OR): 41.531, 95% confidence interval: 1.858-928.304; p=0.019]. Conclusions: Non-invasive prediction for varices by biochemical and radiological methods are reliable methods for screening of cirrhotics patients because of increasing patient overload, when a major chunk of these patients do not show any evidence of varice.